Accounting Practices of Small and Medium Sized Manufacturing Enterprises (SMEs) in Nepalgunj Industrial District - Adhikari, Naba Raj (PYC Nepal Journal of Management, 2020)
The study aims to examine current status of accounting practices in Nepalese small and medium sized manufacturing firms, basing the study on the primary data followed by survey research method. The study concentrated on 18 firms out of 30 manufacturing SMEs as the study area, located in Nepalgunj industrial district. Through self-designed questionnaire comprised into five point Linkert scale, data was collected from managers, owners, and accounting officers of SMEs. The findings revealed that majority of SMEs have been following manual accounting system, and also have been internally preparing their financial accounting statements from accounting experts. In terms of maintaining accounting information, the study reached a conclusion that tax assessment and business performance are key motivational factors. Traditional accounting indicators have got the highest usage, and also viewed as the most usefulness for performance measurement. This study provides more understanding on the accounting practices of manufacturing SMEs that can be used for further research regarding accounting practices in cross industrial district as well as cross country comparisons to provide rich information.